The cobit 5 model for Computer Audit of the academic information systems of the National University Jorge Basadre Grohmann - Aquino Arcata, Rene (2023)
The Jorge Basadre Grohmann National University in its project “IMPROVEMENT OF THE COMPUTER SERVICE OF THE WEB PLATFORM OF THE JORGE BASADRE GROHMANN NATIONAL UNIVERSITY OF TACNA”. in order to improve the quality and integration of the information, its purpose is the implementation of the educational platform. The present research work entitled "The COBIT 5 model for Computer Audit of Academic Information Systems of the Jorge Basadre Grohmann National University", has as a general objective to carry out the necessary guidelines and controls in the use of COBIT 5, for its subsequent maintenance. of the information system in order to achieve operational excellence through a reliable, efficient application of technology.